2000
DOI: 10.1017/s0025315400002320
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of external digestion of crustaceans in Octopus vulgaris paralarvae

Abstract: This paper reports, for the first time, the existence of external digestion of decapod larvae by the common octopus, Octopus vulgaris (Mollusca: Cephalopoda), paralarvae. Zoeae of three crab species were externally digested, leaving a whole and empty exoskeleton. The attack sequence on these prey is also described, and divided into the same three phases (attention, positioning and seizure) already known for Sepia hatchlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…Paralarvae in captivity have been traditionally fed with enriched Artemia (Iglesias et al, 2006) or supplemented with decapod zoeae, copepods, mysids, shrimps, or fish larvae, which increases survival and growth rates (Hernández-García et al, 2000; Iglesias et al, 2004, 2006; Ikeda et al, 2005; Carrasco et al, 2006; Kurihara et al, 2006; Martínez et al, 2014; Farías et al, 2015). Despite all previous attempts, cephalopod paralarval mortality is still close to 100% in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…Paralarvae in captivity have been traditionally fed with enriched Artemia (Iglesias et al, 2006) or supplemented with decapod zoeae, copepods, mysids, shrimps, or fish larvae, which increases survival and growth rates (Hernández-García et al, 2000; Iglesias et al, 2004, 2006; Ikeda et al, 2005; Carrasco et al, 2006; Kurihara et al, 2006; Martínez et al, 2014; Farías et al, 2015). Despite all previous attempts, cephalopod paralarval mortality is still close to 100% in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…Such teeth have been observed also in paralarvae of other cephalopod species (Boletzky 1974;Young et al 1985;Wakabayashi et al 2002;. Experimental studies on paralarvae of O.vulgaris (Hernandez-Garcia et al 2000) showed that they carry out external digestion and ingest the flesh only. The function of teeth at paralarval stage may be related to an adaptation facilitating the suction of the internal fluids of prey (Boletzky 1974; and removal of semidigested prey meat from exoskeleton as reported in adult Idiosepius paradoxus (Kasugai et al 2004).…”
Section: Discussionmentioning
confidence: 88%
“…trituberculatus zoeae and capturing them for ingestion, demonstrating the characteristic feeding behaviour of O. vulgaris paralarvae described by Villanueva, Nozais, and Boletzky (). A large number of zoeae exoskeletons were deposited daily on the filter mesh and tank bottom, the remains of external digestion (Hernández‐García, Martín, & Castro, ; Villanueva, Riba, Ruíz‐Capillas, González, & Baeta, ). These observations suggest that the P .…”
Section: Discussionmentioning
confidence: 99%